2003
DOI: 10.1007/s00381-003-0716-2
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar disc herniation and tight hamstrings syndrome in adolescence

Abstract: Background: Lumbar intervertebral disc herniation is infrequently encountered in children and adolescents. Additional signs and symptoms such as postural deformities and abnormal gait accompany the classical findings of lumbar root irritation. These unusual signs have been described in the literature as "tight hamstrings syndrome". Waddling gait with flexed knees is considered as pathognomonic for this condition and may be masked by the signs of root irritation due to prolapsed intervertebral disc material. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…3 Differential diagnoses include tumour, infection, Schmorl's node, calcification of the posterior longitudinal ligament, calcification of the annulus, limbus fracture, and fracture of the posterior margin of a lumbar vertebral body. [9][10][11] In our cases there was a strong association of adolescent apophyseal ring fracture with a slipped capital femoral epiphysis and overweight/obesity. Being overweight puts persistent and excessive stress on the lumbar spine.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…3 Differential diagnoses include tumour, infection, Schmorl's node, calcification of the posterior longitudinal ligament, calcification of the annulus, limbus fracture, and fracture of the posterior margin of a lumbar vertebral body. [9][10][11] In our cases there was a strong association of adolescent apophyseal ring fracture with a slipped capital femoral epiphysis and overweight/obesity. Being overweight puts persistent and excessive stress on the lumbar spine.…”
Section: Discussionsupporting
confidence: 47%
“…Other symptoms and signs include a limping gait due to listing, para-lumbar muscle spasm and tenderness, restricted back motion, tight hamstrings, a waddling gait with flexed knees, and neurological deficits caused by compressed nerve roots. 9 A systemic enquiry and complete neurological examination is mandatory. Cauda equina syndrome presenting with sphincter disturbance has been reported in apophyseal ring fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors previously suggested that a positive SLR test can result from "tight hamstring syndrome", characterized by the tightness of the lumbar and ischiocrural muscles. 28 Further studies should be conducted to obtain a more precise definition involving a cluster of signs, symptoms, and clinical parameters for predicting NP.…”
Section: Dovepressmentioning
confidence: 99%
“…SLRT can be utilized pre-operatively with diagnostic implications and intra-operatively/post-operatively to confirm the EPD [45,46]. There may be a component of hamstring tightness [47] which may remain; however, the characteristic radicular pain subsides [48]. It is important to note that this is a "passive" SLRT [49] to be performed by the surgeon only and not to be done by the patient on his own.…”
Section: Post-operative Assessmentmentioning
confidence: 99%